Optimization of Lactic Acid Production from Pineapple By-Products and an Inexpensive Nitrogen Source Using Lactiplantibacillus plantarum strain 4O8 - Joel Romial Ngouénam; Pierre Marie Kaktcham; Chancel Hector Momo Kenfack; Edith Marius Foko Kouam; François Zambou Ngoufack (International Journal of Food Science)
Lactic acid (LA) is used in food, cosmetic, chemical, and pharmaceutical industries and has recently attracted much attention in the production of biodegradable polymers. The expensive substances including carbon and nitrogen sources involved in its fermentative synthesis and the increasing market demand of LA have prompted scientists to look for inexpensive raw materials from which it can be produced. This research was aimed at determining the optimum conditions of lactic acid (LA) production from pineapple by-products and an inexpensive nitrogen source using Lactiplantibacillus plantarum strain 4O8. After collection and preparation of the carbon source (pineapple by-products) and nitrogen sources (by-products from fish, chicken, and beer brewing industries), they were used for the formulation of 4 different media in terms of nitrogen sources. Then, the proximate compositions of promising nitrogen sources were determined. This was followed by the screening of factors (temperature, carbon source, nitrogen source, MgSO4, MnSO4, FeSO4, KH2PO4, and KHPO4) influencing the production of LA using the definitive plan. Lastly, the optimization process was done using the central composite design. The highest LA productions (14.64±0.05 g/l and 13.4±0.02 g/l) were obtained in production medium supplemented with chicken and fish by-products, respectively, making them the most promising sources of nitrogen. The proximate analysis of these nitrogen sources revealed that their protein contents were 83.00±1.41% DM and 74.00±1.41% DM for chicken by-products and fish by-products, respectively. Concerning the screening of factors, temperature, nitrogen source, and carbon source were the factors that showed a major impact on LA production in the production medium containing chicken by-products as nitrogen source. A pineapple by-product concentration of 141.75 g/l, a nitrogen source volume of 108.99 ml/l, and a temperature of 30.89°C were recorded as the optimum conditions for LA production. The optimization led to a 2.73-fold increase in LA production when compared with the production medium without nitrogen source. According to these results, chicken by-products are a promising and an inexpensive nitrogen source that can be an alternative to yeast extract in lactic acid production.